Effect of coffee husk compost and liquid organic fertiliser on growth and yield of Capsicum annuum L. var. grossum - Ali, Ramli Moh; Arini , Ni Ayu Komang (Journal of Water and Land Development, 2026)
This study evaluates the synergy between coffee husk compost and Herbafarm liquid organic fertiliser (LOF) as a sustainable alternative to improve growth and yield. The research used a randomised complete block design (RCBD) with two factors: coffee husk compost (0, 80, 90, and 100 g per 10 kg of soil) and Herbafarm LOF (0, 4, 8, and 12 cm3∙dm−3). The compost was prepared over an eight-week period. The process involved chopping coffee husks (600 g∙kg−1) and mixing them with cow dung (300 g∙kg−1) and bran (100 g∙kg−1). The chemical composition of both treatments was analysed prior to application. The following parameters were analysed: plant height, number of leaf, leaf area, stem circumference, total branches, total fruits per plant, harvested fruit weight. Data were analysed using analysis of variance (ANOVA). To ensure validity, assumptions of normality and homogeneity of variance were verified using SPSS software. The results specifically demonstrate that the combination of 100 g compost and 8 cm3∙dm−3 LOF significantly increased leaf area to 88.64 mm2, while 90 g compost combined with 8 cm3∙dm−3 LOF resulted in the highest stem circumference of 4.37 cm. Optimal yields were achieved with 90 g of coffee husk compost, resulting in a fruit weight of 75.47 g per plant. These findings propose a sustainable strategy to utilise coffee husk to reduce environmental pollution and boosting horticultural productivity.